Arterial hypertension clinical course and pathogenesis in patients with impaired glucose tolerance and diabetes mellitus - E. M. Evsikov; V. A. Lusov; O. A. Baykova; Sh. B. Shaparova; Yu. M. Mashukova (Российский кардиологический журнал, 2006)
.